Serum zinc level in Iron Deficiency and Iron Deficiency Anemia of children aged 6 months to 5 years - Karasu, Ece; Erol, Meltem; Yiğit, Özgül; Bostan Gayret, Özlem (Progress in Nutrition, 2018)
Background: Iron Deficiency Anemia (IDA) is the most common anemia in all age groups. The coexistence of iron deficiency anemia and zinc (Zn) deficiency is quite common, for most of the etiologic factors are common. The purpose of this study is to determine the prevalence of zinc deficiency in children with iron deficiency and/or iron deficiency anemia. Method: One hundred and sixty child patients within 6month-5 year age range diagnosed with iron deficiency and/or iron deficiency anemia and 91 children with no iron deficiency and/or iron deficiency anemia diagnosis were included in the study. The relationships between serum zinc levels and other biochemical and hematological parameters were examined. Results: It was observed that the study and control groups had similar demographic characteristics, and there was no statistically significant difference between two groups in terms of average age (months), distribution of age groups, and gender groups. Statistically significant differences were observed between hemoglobin (Hb), haematocrit (Hct), mean corpuscular volume (MCV), red cell distributionwidth (RDW), iron (Fe), total iron binding capacity (TIBC), transferrin saturation (TS) and Ferritin values of the study group and control group, and the cases in the study group were determined to be highly anemic. Statistically significant difference was determined between groups in terms of zinc levels, and zinc levels in the study group were determined to be lower than those in the control group. Zinc deficiency (10%) in children diagnosed with iron deficiency and/or iron deficiency anemia was found more common compared to the control group (2.2%). A positive correlation between serum zinc levels and Hb, Hct, MCV, Fe, TS and Ferritin, and a negative correlation between serum zinc levels and RDW and total TIBC were detected in the study group. Conclusion: According to these results, it was concluded that children with iron deficiency could simultaneously have zinc deficiency, the iron-zinc combination might be more effective for the treatment of iron deficiency than treatment with only iron, and early age supplementation programs might be useful for the highrisk groups such as childhood until zinc deficiency tests gave routine results.